2022
DOI: 10.5171/2022.981169
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Digital Marketing Communication

Abstract: In the 21st century, businesses and communicators have faced new challenges. In the era of modern technology, internationalization and globalization, marketing communication implements new tools, trends and opportunities. Internet and technological development have opened up the potential for two-way marketing communication and online as well as offline communications are required for companies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Marketing communication in the current era is increasingly customer-focused, serving as a crucial process in generating and delivering messages to promote products or services to target audiences [21]. This concept theoretically aligns with Integrated Marketing Communication (IMC), which emerged in the 1990s by Schultz [22].…”
Section: Marketing Communicationsmentioning
confidence: 99%
“…Marketing communication in the current era is increasingly customer-focused, serving as a crucial process in generating and delivering messages to promote products or services to target audiences [21]. This concept theoretically aligns with Integrated Marketing Communication (IMC), which emerged in the 1990s by Schultz [22].…”
Section: Marketing Communicationsmentioning
confidence: 99%
“…Benefits like low cost, ease of access, global approach flexibility and measurability make it more popular among customers. Madan and Rosca (2022) have revealed that due to the transfer of marketing communication, companies need to adjust to modern market trends, while in a modern society; the marketing communication impact is an essential value. Companies need to implement new technologies in their marketing communication in order to be seen worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…It became managerial imperative to cope up with these all set of available alternatives and associated issues of marketing in contemporary period (Leeflang et al, 2014). Digital marketing was a new stage in the evolution of marketing (Madan, 2021) and exists at its embryonic theoretical framing (Novytska et al, 2021). Therefore, different scholars approached it differently (Obitovich, 2022).…”
Section: Introductionmentioning
confidence: 99%